Risk factors for red blood cell alloimmunization in the Recipient Epidemiology and Donor Evaluation Study (REDS‐III) database. (19th April 2018) - Karafin, Matthew S.; Westlake, Matt; Hauser, Ronald G.; Tormey, Christopher A.; Norris, Philip J.; Roubinian, Nareg H.; Wu, Yanyun; Triulzi, Darrell J.; Kleinman, Steve; Hendrickson, Jeanne E.; ,
Summary: Despite the significance of red blood cell (RBC) alloimmunization, the lack of standardized registries in the US has prevented the completion of large studies. Data from 3·5 years of the Recipient Epidemiology and Donor Evaluation Study‐III (REDS‐III) recipient database, containing information from 12 hospitals, were studied. A RBC alloantibody responder had an antibody identified at any point during the study, and a non‐responder had a negative antibody screen at least 15 days post‐RBC transfusion. Demographics, blood type, ICD9/10 codes, and other potential correlates were evaluated. Of 319 177 (2·07%) screened patients, 6597 had a total of 8892 clinically significant RBC alloantibodies identified, with 75% being in the Rh or Kell families. Alloimmunization was more common in females (2·38%) than males (1·68%), and in RhD negative (2·82%) than RhD positive (1·94%) patients. Age, sex, RhD status and race were associated with being a responder, and certain diagnoses (including sickle cell disease or trait, systemic lupus erythematosus, rheumatoid arthritis and myelodysplastic syndrome) were more common among responders than non‐responders. Data collected in this multi‐centre recipient database provide the largest RBC alloimmunized patient cohort studied in the US, with previously known demographic and disease associations of responder status confirmed, and new associations identified.